Assessing the Quality of Organic Fertilizer Products Made from Cow Dung in Wonogiri Regency, Indonesia - Romadhon, Muhammad Rizky; Mujiyo, Mujiyo; Suntoro, Suntoro; Dewi, Widyatmani Sih; Syamsiyah, Jauhari; Rahayu, Rahayu; Widijanto, Hery; Herdiansyah, Ganjar; Herawati, Aktavia; Anggita, Akas; Hasanah, Khalyfah; Hardian, Tiara; Istiqomah, Nanda Mei; Irmawati, Viviana (Agroindustrial Journal, 2023)
Kebonagung Sub-district, Sidoharjo District, Wonogiri Regency is the Wonoagung Wonogiri Organic Farming Association (PPOWW) location. Mitra is an organization engaged in organic rice and cattle cultivation. The conversion of bovine dung into organic fertilizer, particularly liquid fertilizer containing biological agents, is one of the waste elimination strategies employed to prevent environmental contamination. The nutrient content of organic fertilizer material sources varies. Organic fertilizer of high quality conforms to the Standard for Organic Fertilizers established by the Ministry of Agriculture of the Republic of Indonesia. Only some producers are aware of the standard quality requirements for organic fertilizer. It is necessary to analyze the nutrient content of organic fertilizer products to determine whether the quality of organic fertilizer is excellent. A preliminary survey of partner conditions, preparation of materials (organic fertilizer), and analysis of fertilizer content are among the activities performed. The C/N ratio of organic fertilizer is 8.41, and its pH is 7.6. The analysis results indicate that the Wonoagung Wonogiri Organic Agriculture Association's organic fertilizer products meet the liquid organic fertilizer quality standards. This condition demonstrates that the raw materials used in organic fertilizer production are of high quality and that the appropriate procedures have been followed. Adding biological agents to the production of organic fertilizer can enhance the quality of the finished product.